Information Management / The Organizational Dimension - Earl Michael J (Oxford University Press, 1998)
This book provides an authoritative overview and helpful diagnostics of current information management challenges by some of the leading information systems researchers in Europe and the USA. Organizational Horizons, Groupware in Decision Support, Knowledge Strategies: Propositions from Two Contrasting Industries, Business Process Reengineering: A Phenomenon of Organization, Information Systems in Global Business: Evidence from European Multinationals, Mobilizing the Organization, Strategic Information Systems: Some Organization Design Considerations, Innovating with Information Technology, An Organizational Approach to IS Strategy-Making, Organizing the IS Function, Configuring the IS Function in Complex Organizations, The Role of Corporate IT Function in the Federal IT Organization, Mergers: The Role of Information Technology, Managing IT Projects, IT and Organizational Change, The Project Champion, The Project Sponsor, Contemporary Issues in IS Organization, The Changing Environment for IS Professionals: Human Resource Implications, The Hybrid Manager, The Chief Information Officer: Past and Present and Future, Index.